Assessing the Competitiveness of the Philippine Auto Parts Industry - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2007)
The development of the Philippine automotive parts and components sector is critical to the automotive assembly industry. The availability of competitive parts and components that are locally manufactured can significantly contribute to boost the competitiveness of the assembly sector. Given the current state of small and medium manufacturers, making them internationally competitive and linking them with regional production networks are major challenges. Less competitive firms will have to contend with reduced market shares and eventually bankruptcy. The few remaining competitive ones need to define their strategies and the market position that they want to pursue. The government has an important role to play in the firms adjustment process. While increasing economic integration represent market opportunities, penetrating the export market is not easy and does not come automatically. As the firms search for internal ways and exert effort to improve their competitiveness, this must be complemented with active government support.
Keywords: 330; competitiveness; automotive industry; Internationaler Wettbewerb; Branchenentwicklung; Kfz-Industrie; Philippinen